Socialism is Dead! Long Live Socialism! Reflections on the Communist Manifesto - Casiple, Ramon (Kasarinlan: Philippine Journal of Third World Studies, 2009)
The relevance of the Communist Manifesto in the era of global capitalism was questioned following the collapse of the Soviet model of socialism and the failure of socialism elsewhere. The masterwork of Karl Marx and Friedrich Engels foresaw the divergent paths which capitalism will take economies as well as the resulting inequality and poverty amid plenty. In the past 150 years, the correctness of the Manifesto's analysis of the capitalist system and its flaws, the periodic crises of overproduction, its tendencies towards concetration of capital and towards alienation of labor, its devaluation and destruction of every social nexus, and the revolutionary role of the proletarian class has been proven and refuted. Despite its imperfections, the Manifesto is the standard by which all alternative paradigms are measured. If the socialists and socialismcan keep up, the Manifesto may yet liberate humankind from capitalism, perhaps within the next 150 years.